Enzyme Shielding in an Enzyme‐thin and Soft Organosilica Layer. (9th April 2016) - Correro, M. Rita; Moridi, Negar; Schützinger, Hansjörg; Sykora, Sabine; Ammann, Erik M.; Peters, E. Henrik; Dudal, Yves; Corvini, Philippe F.‐X.; Shahgaldian, Patrick
Abstract: The fragile nature of most enzymes is a major hindrance to their use in industrial processes. Herein, we describe a synthetic chemical strategy to produce hybrid organic/inorganic nanobiocatalysts; it exploits the self‐assembly of silane building blocks at the surface of enzymes to grow an organosilica layer, of controlled thickness, that fully shields the enzyme. Remarkably, the enzyme triggers a rearrangement of this organosilica layer into a significantly soft structure. We demonstrate that this change in stiffness correlates with the biocatalytic turnover rate, and that the organosilica layer shields the enzyme in a soft environment with a markedly enhanced resistance to denaturing stresses.